A multi-objective optimisation algorithm for a drilling trajectory constrained to wellbore stability. Issue 1 (2nd January 2022) - Huang, Wendi; Wu, Min; Hu, Jie; Chen, Luefeng; Lu, Chengda; Chen, Xin; Cao, Weihua
Abstract : The design of a trajectory is significant to the efficiency and safety of a drilling process. In this paper, wellbore stability, indicated by the safe mud weight, is introduced as constraints to formulate a drilling trajectory optimisation problem. The upper and lower bounds of the safe mud weight are analysed according to the real data of a well. To solve the optimisation problem with strict constraints, we devise a new multi-objective optimisation algorithm. The devised algorithm takes advantage of inverted generational distance and knee points, and improves the convergence and diversity of the obtained solutions by modifying the selection process. Simulation results show that the devised algorithm is effective on the drilling trajectory optimisation problem constrained to wellbore stability.